Frequency and management of gestational diabetes mellitus according to the new diabetes in pregnancy study group of India guidelines among Sikkimese women attending tertiary teaching hospital of East Sikkim - Singh, Kirti; Rahman, Hafizur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The screening of GDM is important as various pregnancy related complications are associated to it. With early screening and diagnosis, the complications associated with GDM can be reduced. Studies have shown various ethnic groups are at increasing risk of developing GDM with prevalence differing in different ethnicity. No data is available about frequency of GDM in different ethnic women of Sikkim. This study was performed to determine the frequency of GDM and its variation according to different demographic profiles of Sikkimese women. Methods: Pregnant women between 16-34 weeks of gestation, attending antenatal OPD were included for this study. All the patients were subjected to DIPSI recommended 75 gm oral glucose tolerance test. Diagnosis of impaired glucose tolerance was made when plasma glucose of ≥120-140 mg/dl and diagnosis of GDM was made when the plasma glucose of >140 mg/dl as per DIPSI guidelines. Results: A total of 202 consenting pregnant women during 16-34 weeks of pregnancy were evaluated with DIPSI recommended 75 g oral glucose tolerance test. Overall frequency of GDM was 11.9% among the Sikkimese women while 10.9% had impaired results in OGTT. Conclusions: Frequency of GDM was high (12%) in pregnant women attending tertiary hospital of Sikkim. This implies Sikkimese women should be universally screened for GDM. There was also high occurrence of GDM among Lepcha and Bhutia women which need further study to find out the contributing factors in these women.